THE EFFECTIVENESS OF THE HABIT FORMING MODEL IN IMPROVING THE CHARACTER OF STUDENTS AT MI ASH SHALIHIN YAPIS ABEPURA - Wulandari, Algustin; Efendi, Didik (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
This research aims to see how the habit-forming model is applied in character education at MI Ash Shalihin YAPIS Abepura, Jayapura City. This model is important in the education curriculum in Indonesia because it helps instil moral and ethical values in students. This research uses a qualitative approach with a descriptive type of research to describe events that occur. Descriptive research seeks to provide accurate information in the form of words. Qualitative descriptive methods are used to achieve certain goals, with the researcher as the main tool in data collection. This study applied data analysis techniques from the beginning, during, and after data collection to understand the subject objectively. Data reduction is done by summarizing and selecting important elements to investigate patterns and themes. Drawing conclusions results in a clearer explanation or picture of the findings. Data validity checking is done through triangulation, which involves various sources and data collection techniques to ensure the credibility of information. Triangulation is important to validate the data and find differences that may exist through different methods. The results showed that the model successfully improved student discipline, responsibility and empathy by incorporating character-building activities into the daily routine. This research emphasizes how important consistent practice and reflection are in character education and provides a framework for other educational institutions that want to improve their character education programs. The research also emphasizes how important it is for teachers to provide continuous stimulus and response for the habit-forming model to be successful